Treatment of pregnancy-associated venous thromboembolism: position paper from the working group in women’s health of the Society of Thrombosis and Haemostasis (GTH) - Linnemann, Birgit; Scholz, Ute; Rott, Hannelore; Halimeh, Susan; Zotz, Rainer; Gerhardt, Andrea; Toth, Bettina; Bauersachs, Rupert (Vasa, 2016)
. Venous thromboembolism (VTE) is a major cause of maternal morbidity during pregnancy and the postpartum period. However, because there is a lack of adequate study data, management strategies for pregnancy-associated VTE must be deduced from observational stu-dies and extrapolated from recommendations for non-pregnant patients. In this review, the members of the Working Group in Women’s Health of the Society of Thrombosis and Haemostasis (GTH) have summarised the evidence that is currently available in the literature to provide a practical approach for treating pregnancy-associated VTE. Because heparins do not cross the placenta, weight-adjusted therapeutic-dose low molecular weight heparin (LMWH) is the anticoagulant treatment of choice in cases of acute VTE during pregnancy. No differences between once and twice daily LMWH dosing regimens have been reported, but twice daily dosing seems to be advisable, at least peripartally. It remains unclear whether determining dose adjustments according to factor Xa activities during pregnancy provides any benefit. Management of delivery deserves attention and mainly depends on the time interval between the diagnosis of VTE and the expected delivery date. In particular, if VTE manifests at term, delivery should be attended by an experienced multidisciplinary team. In lactating women, an overlapping switch from LMWH to warfarin is possible. Anticoagulation should be continued for at least 6 weeks postpartum or for a minimum period of 3 months. Although recommendations are provided for the treatment of pregnancy-associated VTE, there is an urgent need for well-designed prospective studies that compare different management strategies and define the optimal duration and intensity of anticoagulant treatment.